1981
DOI: 10.1111/j.1365-2621.1981.tb14543.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nisin on the Outgrowth of Clostridium botulinum Spores

Abstract: Nisin, an antibiotic produced by certain strains of Streptococcus lactis, is effective in preventing the outgrowth of Clostridium botuhum spores. Type A C. botulinurn spores were the most resistant to the inhibitory action of nisin requiring 1000-2000 I.U. of nisin/ ml for a 50% inhibition of outgrowth on TPYG agar plates. Type E spores were more sensitive requiring only 50-100 I.U./ml for 50% inhibition of outgrowth on TPYG agar plates. Type B spores displayed an intermediate level of sensitivity requiring 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
1
3

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(48 citation statements)
references
References 11 publications
4
40
1
3
Order By: Relevance
“…Another alternative to improve safety would be to add additional hurdles to products. Biopreservatives, such as nisin and organic acids, are known to have an antibotulinal effect (33,43,45). However, even a slight change in formulation or processing conditions warrants a safety evaluation by challenge tests since the predictive models available to date appear to frequently provide misleading predictions.…”
Section: Discussionmentioning
confidence: 99%
“…Another alternative to improve safety would be to add additional hurdles to products. Biopreservatives, such as nisin and organic acids, are known to have an antibotulinal effect (33,43,45). However, even a slight change in formulation or processing conditions warrants a safety evaluation by challenge tests since the predictive models available to date appear to frequently provide misleading predictions.…”
Section: Discussionmentioning
confidence: 99%
“…(Scott and Taylor 1981;Somers and Taylor 1981;Rayman et al 1983). The missing effect has been explained by the fact that nisin was proved to bind to the food particles (Scott and Taylor 1981;Rayman et al 1983).…”
Section: The Effect Of Nisinmentioning
confidence: 99%
“…(Scott and Taylor 1981;Somers and Taylor 1981;Rayman et al 1983). The missing effect has been explained by the fact that nisin was proved to bind to the food particles (Scott and Taylor 1981;Rayman et al 1983). Nisin has a hydrophobic nature and will therefore adhere to hydrophobic surfaces and be adsorbed by hydrophilic surfaces by electrostatic interactions (Bower et al 1992;Daeschel et al 1992;Joosten and Nunez 1995).…”
Section: The Effect Of Nisinmentioning
confidence: 99%
“…Djenane et al (2005) found higher effect of LAB at 25°C than that of at lower temperatures. It is also mentioned that using LAB as preservative and/or bioprotector could be useful especially at abuse temperatures (Scott & Taylor 1981;Signorini et al 2006;Wessels & Huss 1996). Einarsson & Lauzon (1995) treated shrimps with various bacteriocins from lactic acid bacteria and reported shelf life extension except carnocin UI49.…”
Section: Resultsmentioning
confidence: 99%